Periodontal health status of patients with Maxillary Chronic Rhinosinusitis (Part 1: Clinical study) - Zaki, Sohair M.; Ahmed, Maha Abd.; Hameed, Husam M. (Journal of Baghdad College of Dentistry, 2018)
Background: Periodontal diseases (PD) are inflammatory conditions of the tissues supporting the teeth, most often gingivitis and periodontitis. Maxillary chronic rhinosinusitis (MCRS) is the inflammation of the maxillary sinuses which is last for at least 12 consecutive weeks duration. Aims of study: Distribution of periodontal diseases among patients with Maxillary chronic rhinosinusitis according to gender and age. Materials and methods: Males and females subjects (25-45 years), divided into two groups; 150 patients suffer from MCRS and 130 subjects without MCRS. Clinical periodontal parameters; Plaque Index (PL.I), Gingival Index (G.I), Probing Pocket Depth (PPD), Clinical Attachment Level (CAL) and Bleeding On Probing (BOP) recorded for four sites per tooth except third molars for all subjects, according to this examination groups were divided into four subgroups: clinically Healthy periodontium, Gingivitis, Chronic periodontitis CP.1, when PPD mean is (4-6 mm) and CP.2, when it is (> 6mm). Results: (75.33%) of patients with MCRS had periodontal diseases, highest percentage (48%) had Gingivitis, number of females more than males, percentages of females with clinically Healthy periodontium and Gingivitis were higher. Subjects without MCRS demonstrated highest percentage (56.92%) with clinically Healthy periodontium. Significant and highly significant differences between the 2 groups in PL.I, G.I, PPD and CAL at all subgroups except BOP score1 revealed non significant differences. Conclusion: 75.33% of patients with MCRS have periodontal diseases with greater PL.I, G.I, PPD and CAL when compared with subjects without MCRS. There is relation between periodontal diseases and MCRS.